2019
DOI: 10.1371/journal.pone.0216093
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic photobioreactor for simultaneous observation and cultivation of single microalgal cells or cell aggregates

Abstract: Microalgae are an ubiquitous and powerful driver of geochemical cycles which have formed Earth’s biosphere since early in the evolution. Lately, microalgal research has been strongly stimulated by economic potential expected in biofuels, wastewater treatment, and high-value products. Similar to bacteria and other microorganisms, most work so far has been performed on the level of suspensions which typically contain millions of algal cells per millilitre. The thus obtained macroscopic parameters average cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Many of the microfluidic‐based systems were improved for long‐term cultivation and imaging of microalgal cells simultaneously. These systems/approaches have great potential to elucidate cell activities like photosynthesis, cellular development and behavioral differences of microalgae (Luke et al, 2016; Wang et al, 2016; Y. Wang, Wang, et al, 2019; Westerwalbesloh et al, 2019). For example, the intensity of chlorophyll fluorescence of a single microalgal cell can be measured by fluorescence detection systems integrated with microfluidics.…”
Section: Sorting Cultivation and Harvesting Via Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the microfluidic‐based systems were improved for long‐term cultivation and imaging of microalgal cells simultaneously. These systems/approaches have great potential to elucidate cell activities like photosynthesis, cellular development and behavioral differences of microalgae (Luke et al, 2016; Wang et al, 2016; Y. Wang, Wang, et al, 2019; Westerwalbesloh et al, 2019). For example, the intensity of chlorophyll fluorescence of a single microalgal cell can be measured by fluorescence detection systems integrated with microfluidics.…”
Section: Sorting Cultivation and Harvesting Via Microfluidicsmentioning
confidence: 99%
“…It was observed that, after sorting by RADS, 92.7% of the cells were viable(Wang et al, 2017). Evaluating the results of Raman spectroscopy (chemical composition) and LIBS (basic composition) measurements together provide a more accurate selection and environmental impact assay with complete biochemical composition of algal biomass(Pořízka et al, 2012;Pořízka et al, 2014).2.2 | CultivationMany of the microfluidic-based systems were improved for longterm cultivation and imaging of microalgal cells simultaneously.These systems/approaches have great potential to elucidate cell activities like photosynthesis, cellular development and behavioral differences of microalgae(Luke et al, 2016;Wang et al, 2016;Westerwalbesloh et al, 2019). For example, the intensity of chlorophyll fluorescence of a single microalgal cell can be measured by fluorescence detection systems integrated with microfluidics.…”
mentioning
confidence: 99%
“…In laboratory conditions, microalgae are grown using dedicated instruments in growth media, which provide the nutrients and water [2] , [3] . These instruments vary in size between microfluidic [4] , [5] and industrial scale implementations [3] , [6] . Their purpose is to agitate and illuminate the cultures.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…In these three platforms, a co-culture can be easily realized via the introduction of pre-mixed microbes. Microtraps have been designed to trap algal cells using size restriction with the dimension of the trap size in the order of a few micrometers for cell growth study [20][21][22]. This method works well with a monolayer of trapped cells perfused with media through connected channels, and have been used successfully in studies of synthetic bacteria co-cultures [23,24].…”
Section: Modeling Microbial Community Organizationmentioning
confidence: 99%